Qualitative Study: Health Empowerment Model of Suku Anak Dalam (SAD) Along the Central Crossing Sumatera Indonesia - M.Ridwan; Ummi Kalsum; Rd. Halim (Universitas Airlangga, 2025)
Background: Health problems are still a major issue for the Suku Anak Dalam (SAD). Knowledge of health, personal hygiene, trust with migrants, desire to improve themselves and economic ability are still obstacles to healthy living. Efforts have been made but have not shown maximum results. Objectives: The research aims to find strategies for empowerment approaches to improve healthy behavior for SAD along the Central Cross of Sumatera. This research is expected to produce an empowerment strategy to improve health and enable people to behave healthily. Methods: The research design for this study is qualitative, with 43 informants consisting of the Public Health Department, Public Health Center, tumenggung, jenang, Pundi Sumatra NGOs, and SAD residents in four residential areas of the research location. Data collection was done using in-depth interviews and observations. The research locations are in Sarolangun District, Merangin, and Bungo Jambi District. Results: Health empowerment research conducted by the Health Service and Community Health Centers has been carried out with outreach activities, free treatment, and reproductive health, but has not shown success because no special SAD assistants are living in the settlement to provide examples of the healthy behavior they expect. Empowerment is carried out by non-governmental organizations (NGOs) with a strategy of providing special workers as companions in residential locations so that they can meet the needs of the community along with other stakeholders and can increase community trust so that it is easier for community mobilizers to accept change. Conclusion: The strategy of the health empowerment approach is to prepare a companion for each group who lives with them and understands sufficient health knowledge. Tumenggung's role as a mobilizer is becoming a key figure in the SAD community movement.